Detection, stratification and treatment of hepatitis C–positive prisoners in the United Kingdom prison estate: Development of a pathway of care to facilitate the elimination of hepatitis C in a London prison. Issue 10 (15th June 2020) - Connoley, Declan; Francis‐Graham, Seth; Storer, Michelle; Ekeke, Nnenna; Smith, Claire; Macdonald, Douglas; Rosenberg, William
Abstract: The United Kingdom is committed to eliminating hepatitis C virus (HCV) infection by 2025. The prison estate provides an opportunity to identify and treat HCV‐positive individuals in a high‐prevalence environment. We designed and implemented a pathway of care within a London prison to diagnose, stratify and link HCV‐positive prisoners into care. This study was a two‐phase case study of a HCV care pathway. New arrivals to the prison were offered blood‐borne virus screening with dried blood spot testing at their secondary health check. Those with active infection completed disease stratification tests and were reviewed at a weekly hospital‐based multidisciplinary team meeting to determine management. In Phase‐2, the pathway was redesigned to improve testing and the referral of HCV‐positive prisoners into treatment. Over the 30‐month evaluation period, 12, 946 people were received in the prison. During Phase‐1, 19.6% of new arrivals completed blood‐borne virus testing, with 7.3% identified as HCV‐positive. Just 8.3% of HCV‐positive individuals were treated or referred for treatment in Phase‐1. During Phase‐2, 30% of new receptions completed BBV testing and 3.9% were identified as HCV‐positive. Linkage into care was improved, with 38.9% treated or referred during the second phase. Poor access to testing and referral to treatment limit the effectiveness of care provision for prisoners with HCV. Elimination of HCV in prisons requires local service configuration to ensure high uptake of testing, with all HCV‐positive cases then offered treatment during custody or referral on to treatment after release. Abstract : We designed and implemented a pathway of care within a UK prison to diagnose, stratify and link into care HCV‐positive prisoners. Poor screening and treatment rates hampered this HCV‐eradication programme; however once referred to secondary care, treatment and linkage into care were adequate. More dedicated prison security and healthcare workers are required for prison‐based HCV elimination programmes to assist HCV eradication by 2030.